“Saturday Night Palsy”: Lessons from a Patient - Sarmento de Beires, Teresa; Eiras, Andreia (Gazeta Médica, 2023)
“Saturday night palsy”, also known as “lovers’ paralysis”, is a neuropathy of the radial nerve, caused by extrinsic compression at a certain point in its path along the humerus, usually at the level of the spiral groove. This designation is based on the fact that this compression occurs, frequently, after excessive alcohol intake, thus resulting in an incorrect position of the arm during sleep. This is the fourth most common mononeuropathy worldwide, affecting about 2.97 per 100 000 men and 1.42 per 100 000 women. Paralysis of the radial nerve causes loss of sensory and/or motor functions, depending on where the nerve was injured. The following case refers to a patient observed in an acute consult in a Primary Care Unit, after waking up with his right-hand hanging. In this report, the deficit shown by the patient allowed the authors to infer the location of the injury.